2005
DOI: 10.1002/ana.20504
|View full text |Cite
|
Sign up to set email alerts
|

Sparse multifocal stimuli for the detection of multiple sclerosis

Abstract: We compared the diagnostic capabilities of contrast reversal and sparse pattern pulse stimulation for dichoptic multifocal visual evoked potentials (mfVEPs) measured in normal subjects and multiple sclerosis (MS) patients. Multifocal responses were obtained from 27 normal subjects and 50 relapsing-remitting patients, 26 of whom had experienced optic neuritis (ON+). The patient groups were matched for length of disease and number of clinical attacks. Compared with the responses of normal subjects those of MS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 26 publications
4
66
2
Order By: Relevance
“…However, it should be possible to substantially shorten the mfVEP test for clinical purposes. For example, Ruseckaite et al [16] reported a sensitivity/specificity of 92%/ 100% using a sparse mfVEP paradigm and under 3 min of recording. In any case, cVEP testing is more readily available than mfVEP testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be possible to substantially shorten the mfVEP test for clinical purposes. For example, Ruseckaite et al [16] reported a sensitivity/specificity of 92%/ 100% using a sparse mfVEP paradigm and under 3 min of recording. In any case, cVEP testing is more readily available than mfVEP testing.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not unreasonable to assume that although the cVEP may detect wide-spread areas of demyelinization, it may fail to detect localized changes. Using the sparse stimulus mfVEP paradigm, developed by James and colleagues [14][15][16], Ruseckaite et al [16] estimated a 92% sensitivity, with a specificity of 100%, for detecting MS. However, their results were not compared to cVEP recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Multifocal VEP responses with dichoptic stimulation have been recorded before using a liquid crystal polarizing shutter with associated polarizing spectacles [12,[17][18][19]. The method reported by us, however, does not require the patient to wear polarizing glasses (which dramatically reduce stimulus luminance), and uses portable virtual reality goggles rather than the large monitor screen.…”
Section: Discussionmentioning
confidence: 98%
“…Sato et al [16] reported that pseudorandom binary sequences (PRBS) could be used to independently stimulate right and left eyes, and the response of each eye could be calculated by crosscorrelating the resultant response with the PRBS. Recently, James and co-workers [12,[17][18][19] reported recording multifocal (8 or 60 regions) pattern VEP for each eye under dichoptic stimulation conditions using a liquid crystal polarizing shutter and associated polarizing spectacles, which, however, significantly reduces luminance of the stimulus. The current study further explores the possibilities and nuances of recording mfVEP from each eye under dichoptic testing conditions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation